Factors Influencing Consumer Purchasing Behaviour: A Study of Honda - Singh, Esha Kaur A/P Jaswent; Valin, Eyep Kay; Tony, Elyana Anak; Binti Zulhelmi, Ezreen Dayana; Gautam, Mayank; Dema, Wangden; Nabila, Belinda; Agiasari, Nabella Putri; Teoh, Dr. Kok Ban; Yusof, Dr. Rosmelisa (Asia Pacific Journal of Management and Education (APJME), 2023)
Honda is a competitive brand in the automobile industry with a growing popularity among the public. Hence, Honda has always tried to innovate and make its product different from others which are still preferred by the public. The purpose of this study is to identify the factors that are influencing consumer purchasing behaviour towards Honda cars to provide useful insights regarding the buying pattern of consumers to assist the management in their future marketing strategies. The factors that affect customers purchasing behaviour towards Honda’s vehicle are price, service quality, perceived usefulness and brand loyalty. The research was conducted through primary data sources such as surveys and secondary data sources such as website research. We employed a quantitative research method, surveyed and collected data from 160 participants through an online survey questionnaire. The findings showed that customers are concerned about the brand loyalty and service quality the most while purchasing Honda vehicles. These are helpful for the company to implement strategies and grasp more customers as well as continuous improvement towards its performance.